2017
DOI: 10.1007/s00428-017-2213-0
|View full text |Cite
|
Sign up to set email alerts
|

DNA degrades during storage in formalin-fixed and paraffin-embedded tissue blocks

Abstract: Formalin-fixed paraffin-embedded (FFPE) tissue blocks are widely used to identify clinically actionable molecular alterations or perform retrospective molecular studies. Our goal was to quantify degradation of DNA occurring during mid to long-term storage of samples in usual conditions. We selected 46 FFPE samples of surgically resected carcinomas of lung, colon, and urothelial tract, of which DNA had been previously extracted. We performed a second DNA extraction on the same blocks under identical conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
80
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 24 publications
4
80
1
Order By: Relevance
“…These observations corroborated with those reported in previous studies demonstrating that DNA degradation is more evident in FFPE samples than in FF samples owing to the fragmentation and chemical modification of DNA . The sample storage period also reportedly influences DNA degradation in FFPE samples . In the current study, the sample storage period was inversely correlated with the DNA library concentration (r = ‐0.4, p < .01; supplemental online Fig.…”
Section: Discussioncontrasting
confidence: 57%
“…These observations corroborated with those reported in previous studies demonstrating that DNA degradation is more evident in FFPE samples than in FF samples owing to the fragmentation and chemical modification of DNA . The sample storage period also reportedly influences DNA degradation in FFPE samples . In the current study, the sample storage period was inversely correlated with the DNA library concentration (r = ‐0.4, p < .01; supplemental online Fig.…”
Section: Discussioncontrasting
confidence: 57%
“…The present study has the following limitations. First, the specimens used in this study were lung tissues from autopsied malaria patients that had been stored for approximately 30 years and were thus unsuitable for determining the gene expression levels of SphK-1 and S1PR-3 via molecular techniques [35]. Second, it was not possible to determine the time course of SphK-1 and S1PR-3 expression during the malaria infection.…”
Section: Discussionmentioning
confidence: 99%
“…Given the age of this specimen (approximately 9 years), time-dependent DNA degradation likely impacted PCR amplification. A recent study demonstrated that, compared with DNA immediately extracted from FFPE tissue, archived samples stored for a mean of 5.4 years had 53% lower DNA quantity and only 11% of the original DNA could be amplified by real-time PCR (14). Time-dependent effects on DNA quality from biopsy specimens are predicted to be even greater.…”
Section: Discussionmentioning
confidence: 99%